Romanticism and Rebellion: Coleridge’s Poetic Resistance to the Enlightenment through The Rime of the Ancient Mariner - Pratiwi, Dyani Prades; Qarimah, Aryana Nurul (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Andalas, 2025)
This research aims to see the romanticism contained in the poem and uses descriptive qualitative as the method. The results of this research are characteristics from the romantic era, which are nature, freedom, supernatural, and gothic. The choice of supernatural and gothic themes came from Coleridge's childhood memories of folk oral traditions as a child;